Self Control dan Self Care Behaviour pada Penderita Hipertensi - Diana Rachmania; Andika Siswoaribowo; Puput Novitasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Chronic disease causes hypertension sufferers to feel lazy to do self-care behavior, this happens because of helplessness and a sense of hopelessness that makes hypertension sufferers unable to control themselves. In each individual there is self-control to focus on the process of controlling individual behavior to lead a healthier life. The design of this study is a correlation with a cross-sectional approach, with a purposive sampling technique, obtained a sample of 64 respondents with a population of 76 respondents. The instruments used in this study were the SCS questionnaire for self-control and the HPB-SCP for self- care behavior. The results showed that half of the respondents (50%) had high self-control. Meanwhile, almost half of the respondents (43.8%) have good self-care behavior. Analysis of spearmen's rank test data p-value 0.000 <0.05 showed that there was a relationship between self-control and self-care behavior in hypertension sufferers in Malasan Village, Durenan District, with a strong relationship category (r = 0.809). This means that the correlation coefficient is positive, the relationship between the two variables is unidirectional. The higher the self-control, the better the self-care behavior in people with hypertension. With the self-control ability possessed by hypertension sufferers, it will have a different effect on self-care behavior. People with hypertension should increase self-control to resist temptations such as unhealthy food or lazy to exercise. It is hoped that people with hypertension will be disciplined in taking medication so that their blood pressure remains normal.